Modeling and synthesis of bifunctional dual activation thiourea organocatalysts for Michael addition of pyrazole - Savita Sharma; Vandana Sharma; Sanjay Mandal; Raj K. Bansal (Tetrahedron Green Chem)
Modeling of Michael addition of pyrazole to cinnamaldehyde in the presence of six thiourea catalysts has been done at the DFT (B3LYP/6-31+G(d,p)) level. Four catalysts incorporating 2-pyridyl moiety are found to exhibit bifunctional dual activation by encapsulating pyrazole molecule in the cavity of cinnamaldehyde-catalyst complex thereby mimicking biosystem to bring the two reactants closer and also narrowing down the HOMO-LUMO gap. Guided by the theoretical results, four new N-bis(3,5-trifluoromethyl)phenyl-N′-2-pyridylthiourea catalysts were synthesized and well characterized on the basis of IR, 1H and 13C NMR and HRMS studies. X-ray crystal structure of one catalyst could also be done. On determining comparative catalytic efficacies of these catalysts experimentally for the model reaction of pyrazole with cinnamaldehyde, the catalyst N-bis(3,5-trifluoromethyl)phenyl-N′-2-(5-chloropyridyl)thiourea was found to be most effective, which is in accordance with the theoretical modeling results.